2019
DOI: 10.1248/bpb.b19-00185
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Cytostatic Effects of BCR-ABL Tyrosine Kinase Inhibitors (TKIs) after Washout in Human Leukemic K562 Cells

Abstract: Tyrosine kinase inhibitors (TKIs) are used as the first choice for chronic myeloid leukemia (CML) pharmacotherapeutics. Some patients taking these drugs showed good therapeutic reactivity despite the disappearance of drugs from blood. We investigated whether these drugs have sustained effects even after their disappearance and whether their effects depend on their amounts of intracellular accumulation. Cell proliferation after exposure of K562 cells or Multidrug resistance-1 (MDR-1)-transfected K562 cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…1 mL sample (after trypsinization for MCF-7) was taken from the plaque on the last day of the culture for control and experimental groups and this sample was used for cell count and viability. 13,14 Cell Count, Viability Test and MTT Test By taking 10 µL of the obtained cell solution, the cells were counted under the light microscope (Olympus BX51, Tokyo, Japan) using the Thoma cell counting chamber (Arat et al, 2008). Acridine Orange (Sigma, A6014, Germany) viability assay was used to measure the viability of cells.…”
Section: Methodsmentioning
confidence: 99%
“…1 mL sample (after trypsinization for MCF-7) was taken from the plaque on the last day of the culture for control and experimental groups and this sample was used for cell count and viability. 13,14 Cell Count, Viability Test and MTT Test By taking 10 µL of the obtained cell solution, the cells were counted under the light microscope (Olympus BX51, Tokyo, Japan) using the Thoma cell counting chamber (Arat et al, 2008). Acridine Orange (Sigma, A6014, Germany) viability assay was used to measure the viability of cells.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, it is quite unlikely that the plasma concentration was in the therapeutic range. Aoyama et al 8 recently observed in a K562 cell line model that the cytostatic effect (depending on intracellular accumulation) of imatinib, nilotinib, or dasatinib persists even after the disappearance of the drug in the plasma. The therapeutic effects of TKIs are primarily based on their intracellular activity, plasma concentrations being only an indirect but useful marker.…”
mentioning
confidence: 99%